Associations between feeding practices and maternal and child weight among mothers who do and do not correctly identify their child's weight status - R. G. Tabak; C. D. Schwarz; D. L. Haire‐Joshu (Wiley, 2017)
Summary Objective This study aimed to explore factors associated with accuracy of maternal weight perception and determine if maternal feeding practices are associated with weight status. Methods Overweight/obese mothers reported demographics and perception of their child's weight and completed a modified preschooler feeding questionnaire. Mother's and child's height and weight were measured. Logistic regression was used to explore associations between demographic factors and accuracy. Correlations between the preschooler feeding questionnaire scales and mom's body mass index (BMI) and child's BMI‐percentile were explored for the total sample and accurate and underestimating moms. Results Among mothers whose child was overweight or obese, only 20% of mothers correctly identified the child as overweight. Forty percent of moms were underestimaters. There was a positive correlation between concern the child was overweight/overeating and the child's BMI‐percentile among underestimating moms; in the total sample (r = 0.32, p < .001) and accurate moms (r = 0.52, p < .001). In underestimaters only, there was a negative relationship between child BMI‐percentile and pressure to eat (r = −0.30, p < .001) and concern about child underweight (r = −0.47, p < .001). Conclusions This study identified different associations between child weight and mother's feeding practices in mothers accurately and inaccurately perceiving her child's weight. Intervention studies should explore targeting education on feeding practices based on these perceptions.